High-Performance Control of a DC–DC Z-Source Converter Used for an Excitation Field Driver - Amodeo, Santiago Jose (2012)
The electromechanical interface is a Synchronous Machine because its field winding permits direct management of the magnetization during speed variations. For systems with a common dc-link for the drive and excitation converters, the efficiency is increased if the excitation drive has boosting capability. It is shown that with the proposed control strategy the Z-source converter is suitable for this application, becoming a better alternative than the typically usedbuckconverter. The Z-source converter in combination with the proposed multi-loop control law can achieve the desired voltage reference swing and high-performance tracking. An analytical comparison between the dominant losses of the buck topology, typically used in FESS, and the Z-source converter shows that the latter has higher efficiency for this application. The parameters of the converter prototype were experimentally identified and used to implement the proposed controller. The control strategy uses the two duty cycles as manipulated variables, one to allow tracking fast changes in the reference signal and the other to adapt the system to the slow changes. The combined action on both inputs contribute to the compensation of the non-minimum phase response of the Z-converter. Experimental results show the potential of the controller for tracking typical FESS application waveforms.